(untitled) (Research, Society and Development, 2026)
Telepharmacy is becoming a common practice worldwide, contributing to improved treatment adherence, rational use of medications, and the strengthening of patient self-care, especially during crises. This is a scoping literature review aimed at gathering evidence on the effectiveness and tools that can support the clinical practice of pharmaceutical care via telepharmacy for patients with Chronic Obstructive Pulmonary Disease (COPD) and asthma. The PubMed, Scopus, and Lilacs databases were used in conjunction with the descriptors "pharmaceutical care," "telepharmacy," "teleconsultation," "COPD," and "asthma," combined with Boolean operators to search for articles. Studies in Portuguese, English, Spanish, and French were included, without temporal restrictions, that addressed pharmaceutical interventions in patients with COPD or asthma via telepharmacy. After applying the selection and eligibility criteria, 10 articles were selected for final analysis. Pharmaceutical interventions performed through telepharmacy contribute to symptom control, treatment adherence, and improved inhalation technique. These findings reinforce the use of remote pharmaceutical care as a strategy to support the management of diseases such as COPD and asthma, and for populations that have difficulty accessing in-person care at health units. It is concluded that telepharmacy presents itself as a viable and promising tool for expanding the provision of pharmaceutical care, promoting adherence, correct execution of inhalation techniques, and disease control.